2014
DOI: 10.1111/age.12122
|View full text |Cite
|
Sign up to set email alerts
|

Identifying chromosomal selection‐sweep regions in facial eczema selection‐line animals using an ovine 50KSNP array

Abstract: Facial eczema (FE) is a hepato-mycotoxicosis found mainly in New Zealand sheep and cattle. When genetics was found to be a factor in FE susceptibility, resistant and susceptible selection lines of Romney sheep were established to enable further investigations of this disease trait. Using the Illumina OvineSNP50 BeadChip, we conducted a selection-sweep experiment on these FE genetic lines. Two analytical methods were used to detect selection signals, namely the Peddrift test (Dodds & McEwan, 1997) and fixation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…A total of 49 517 SNPs, 91.30% of SNPs on the chip, met the quality-control measures and had a MAF >0.01 across all samples. These results are similar to other ovine studies, which reported >98% and >90% for sample and SNP loci call rates, respectively Shariflou et al, 2012;Våge et al, 2013;Phua et al, 2014).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…A total of 49 517 SNPs, 91.30% of SNPs on the chip, met the quality-control measures and had a MAF >0.01 across all samples. These results are similar to other ovine studies, which reported >98% and >90% for sample and SNP loci call rates, respectively Shariflou et al, 2012;Våge et al, 2013;Phua et al, 2014).…”
supporting
confidence: 91%
“…The RRS was carried out on 60 individuals from 15 breeds . The SNP chip has been validated in more than 75 international sheep breeds and has been used in a wide range of applications, which include the elucidation of quantitative trait loci and selection strategies (Miller et al, 2011;Kijas et al, 2012;Demars et al, 2013;Liu et al, 2013;Våge et al, 2013;Gutiérrez-Gil et al, 2014;Phua et al, 2014). SNP panels developed from a limited number of individuals or breeds are not necessarily representative of the polymorphisms and frequency distribution of alleles in the genome of all members of the species, this being referred to as ascertainment bias (Nielsen & Signorovitch, 2003;Morin et al, 2004).…”
mentioning
confidence: 99%
“…) and screening for selection signatures on the genomes of FE‐resistant and susceptible genetic‐line animals (Phua et al . ). To date, eight putative loci located on different chromosomes have been identified to be involved in the disease trait (Phua & Dodds ).…”
Section: Introductionmentioning
confidence: 97%
“…Several approaches have been used to search for causative genes or loci underlying FE tolerance, including a candidate gene approach [31,32], genome-wide scans for quantitative trait loci (QTL) [33,34] and scanning for selective sweep signatures [35]. There was limited concordance between the results of the studies, with only two of the selective sweep regions, on chromosomes OAR1 and OAR13, found within suggestive (F-statistic value>10.2) QTL regions.…”
Section: Introductionmentioning
confidence: 99%